Energy networks in the energy transition era - Rahmatallah Poudineh (The Oxford Institute for Energy Studies, 2022)
As infrastructures that connect the energy source with the energy use, energy networks constitute a crucial element of national and global energy systems. They also play a key role in helping with balancing supply and demand, thus ensuring that energy is not only available in the right places but also at the right time. Energy transition will have significant impacts, though not necessarily in the same way, on existing energy networks, for example, electricity and natural gas grids, and might lead to the growth of new energy carrier systems, such as district heating and cooling and the deployment of new infrastructures to support the use of hydrogen. Understanding the implications of energy transition for energy networks, and the ways in which these infrastructures should adapt to the challenges of decarbonization, is important to achieve net-zero carbon objectives. This paper explores some of the key issues faced by electricity transmission and distribution networks; natural gas networks; and future hydrogen, heating, and cooling networks in the transition of energy systems. Also, as future decarbonized energy systems are likely to exhibit significantly more interaction between different parts of the system, this paper explores possible approaches to utilizing the synergies between energy networks and benefiting from their integrated operation to lower the costs and challenges of decarbonization.
Keywords: 330; Electricity distribution networks; electricity transmission networks; energy networks; Energy Transition; heating and cooling networks; hydrogen networks; integrated energy networks; natural gas networks